2020
DOI: 10.3390/nu12051460
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Status and Deposition in Neonatal and Weanling Rats Reared by Mothers Consuming Normal and High-Fat Diets with Adequate or Supplemented Vitamin A

Abstract: The circulating level of vitamin A (VA; retinol) was reported to be lower in obese adults. It is unknown if maternal obesity influences the VA status of offspring. The objective of the study was to determine the VA status and deposition of neonatal and weanling rats reared by mothers consuming a normal or high-fat diet (NFD or HFD) with or without supplemented VA. Pregnant Sprague-Dawley rats were randomized to an NFD or HFD with 2.6 mg/kg VA. Upon delivery, half of the rat mothers in the NFD or HFD cohort wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…As presented in our previous publication ( 31 ), the total retinol concentration in the milk separated from rat pups’ stomach was significantly higher in the NFD + VA and HFD + VA groups than in their respective controls (∼20-fold increase; P < 0.05), indicating that rat pups in VA-supplemented groups received significantly more VA. No significant difference was noted between the NFD and the HFD group or between the NFD + VA and the HFD + VA group. The serum total retinol concentration was also significantly ( P < 0.01) higher in the VA-supplemented groups than in the nonsupplemented groups at all 3 time points, confirming the effectiveness of VA supplementation in raising pups’ VA status.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…As presented in our previous publication ( 31 ), the total retinol concentration in the milk separated from rat pups’ stomach was significantly higher in the NFD + VA and HFD + VA groups than in their respective controls (∼20-fold increase; P < 0.05), indicating that rat pups in VA-supplemented groups received significantly more VA. No significant difference was noted between the NFD and the HFD group or between the NFD + VA and the HFD + VA group. The serum total retinol concentration was also significantly ( P < 0.01) higher in the VA-supplemented groups than in the nonsupplemented groups at all 3 time points, confirming the effectiveness of VA supplementation in raising pups’ VA status.…”
Section: Resultssupporting
confidence: 68%
“…It may indicate that maternal HFD consumption can potentially compromise the effects of antioxidants in improving redox status. Our previously published data ( 31 ) indicated that the HFD + VA group possessed significantly more VA than the NFD + VA group, supporting the potential role of WAT as a reservoir for dietary lipophilic antioxidants and micronutrients. This was further supported by the significantly positive correlation found between the lipophilic AC and the VA mass in the WAT.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations